The Influence of Leadership Style on Employee Commitment in The Organization Through Employee Job Satisfaction as an Intervening Variable at PT Industri Kapal Indonesia (Persero) Kota Makassar - Natsir, Uhud Darmawan; Rizkullah, Rifki Rif'at; Aswar, Nurul Fadilah (Economics and Business Journal (ECBIS), 2026)
The Influence of Leadership Style on Employee Commitment in the Organization through Employee Job Satisfaction as an Intervening Variable at PT Industri Kapal Indonesia (Persero) Makassar City. This study aims to examine the influence of leadership style on employee commitment in the organization with employee job satisfaction as an intervening variable in PT Industri Kapal Indonesia (Persero) Makassar City. This study uses a quantitative approach with the type of associative research. The population in this study is all employees of PT Industri Kapal Indonesia (Persero) Makassar City which is 132 people, so the sampling technique used is the census method. Data collection was carried out through the distribution of questionnaires to respondents. The data obtained was then analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software version 3.0. The results of the study show that leadership style has a positive and significant effect on employee commitment in the organization. In addition, leadership style has been proven to have a positive and significant effect on employee job satisfaction. Employee job satisfaction also has a positive and significant influence on employee commitment in the organization. Furthermore, the results of the testing of the intervening variables showed that employee job satisfaction was significantly able to mediate the influence of leadership style on employee commitment in the organization.